The Holly Bough service at Liverpool Cathedral and psychological type theory: Fresh expressions or inherited church? - Francis, Leslie J. (HTS teologiese studies, 2020)
One of the key intentions of fresh expressions of church is to reach the kind of people inherited church find it hard to reach. Psychological type profiling of church congregations has demonstrated that Anglican churches have particular difficulty in reaching those whose Jungian judging preference is for thinking rather than for feeling. Studies that have explored the psychological type profile of participants within fresh expressions suggest that they do not significantly differ from inherited congregations in terms of reaching thinking types. Two previous studies, however, have reported higher proportions of thinking types attending cathedral carol services. The present study among 441 individuals attending the Holly Bough service in Liverpool Cathedral also found a higher proportion of thinking types among the participants. These findings suggest that cathedral carol services may be functioning as fresh expressions of church in a significant way.Contribution: Situated within the science of cathedral studies, rooted in psychological type theory, and drawing on data from 441 attendees at the Holly Bough service, this study demonstrates that cathedral services at Christmas are more successful than either inherited church or fresh expressions of church in reaching thinking types.